Induction of antigen-specific CD8+ T cells, T helper cells, and protective levels of antibody in humans by particle-mediated administration of a hepatitis B virus DNA vaccine. - Roy, M; Wu, MS; Barr, L; Fuller, J; Tussey, L; Speller, S; Culp, J; Burkholder, J; Swain, W; Dixon, R; Widera, G; Vessey, R; et al. (2000)
A DNA vaccine against the hepatitis B virus (HBV) was evaluated for safety and induction of immune responses in 12 healthy, hepatitis-naïve human volunteers using the needle-free PowderJect system to deliver gold particles coated with DNA directly into cells of the skin. Three groups of four volunteers received three administrations of DNA encoding the surface antigen of HBV at one of the three dose levels (1, 2, or 4 microg). The vaccine was safe and well tolerated, causing only transient and mild to moderate responses at the site of administration. HBV-specific antibody and both CD4+ and CD8+ T cell responses were measured before and after each immunization. All the volunteers developed protective antibody responses of at least 10 mIU/ml. In volunteers who were positive for the HLA class I A2 allele, the vaccine also induced antigen-specific CD8+ T cells that bound HLA-A2/HBsAg(335-343) tetramers, secreted IFN-gamma, and lysed target cells presenting a hepatitis B surface antigen (HBsAg) CTL epitope. Enumeration of HBsAg-specific T cells producing cytokine indicated preferential induction of a Type 1 T helper cell response. These results provide the first demonstration of a DNA vaccine inducing protective antibody titers and both humoral and cell-mediated immune responses in humans.